Validity and Reliability Studies of the Indonesian Version of Heart Failure Somatic Perception Scale (HFSPS) Questionnaire - Okviasanti, Fanni; Yusuf, Ah.; Kurniawati, Ninuk Dian (International Journal of Psychosocial Rehabilitation, 2020)
— Heart Failure Somatic Perception Scale (HFSPS) is one of the most commonly used questionnaires to assess HF physical symptoms. However, to be utilized in Indonesia, it needs validity and reliability studies. This study aimed to obtain a valid and reliable Indonesian version of the Heart Failure Somatic Perception Scale (HFSPS) so that it can be used in Indonesia. This study was a cross-sectional study with 152 subjects with a mean age of 58.03±10.2 years who had heart failure disease and were treated at the outpatient clinic of cardiology in Government Hospital in Lamongan and Gresik, East Java, Indonesia. The validity of the HFSPS was assessed by evaluating the construct validity using a multitrait-multimethod analysis and external validity was evaluated by comparing the HFSPS with the MLHF questionnaire. Reliability was assessed using Cronbach’s α. All items in the Indonesian version of the HFSPS questionnaire were valid and had a positive strong correlation with the MLHF questionnaire (r=0,635; p<0.000). The Cronbach α of the Indonesian version of HFSPS was 0.813. The Indonesian version of HFSPS has good validity and reliability to assess the physical symptoms of patients with chronic heart failure in Indonesia.